Upcycling of waste polycarbonate into polyallyls for degradable high-performance BMI/polyallyl-based thermosets/CFRPs - Che-Wei Lin; Lu-Ling Chen; Dula Daksa Ejeta; Ching-Hsuan Lin (Chemical Engineering Journal, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Uncovering hidden β-adrenergic agonist exposure from meat consumption through nationally representative human biomonitoring in Taiwan - Ho-Tang Liao; Tzu-Hsuan Peng; Chien-Jen Wang; Jing-Fang Hsu; Ching-Chun Lin; Wen-Harn Pan; Shu-Lih Chia; Pau-Chung Chen (International Journal of Hygiene and Environmental Health, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Injectable near-infrared–responsive silk fibroin nanocomposite hydrogel enabling spatiotemporally controlled photothermal chemotherapy - Ling-Chu Yang; Ching-Wen Hwang; Shao-Hsuan Tsao; Hsin-Yao Lin; Yunching Chen; Dehui Wan (Chemical Engineering Journal, 2026)

Formononetin protects against oxaliplatin-induced peripheral neurotoxicity via Nrf2/HO-1 antioxidant pathway without impairing anticancer efficacy - Yang-Chen Chang; Wan-Hsuan Lin; Horng-Huey Ko; Yi-Ching Lo; Hsun-Shuo Chang; Hui-Ching Lin; Yih-Fung Chen (NeuroToxicology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Fabrication of superwetting gelatin/phytic acid/cellulose composites with antibacterial characteristics for separating complex contaminants from wastewater - Guyita Berako Belachew; Chien-Chieh Hu; Chih-Feng Wang; Mei-Yi Liao; Wei-Song Hung; Ching-Hsuan Lin; Shiao-Wei Kuo; Juin-Yih Lai (Journal of Water Process Engineering, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Upcycling waste PET into benzoxazines with simultaneously low curing temperatures and high thermal stability - Dula Daksa Ejeta; Meng-Xuan Li; Yu-Kuan Hsu; Muhammad Javed Iqbal; Ching-Hsuan Lin (Chemical Engineering Journal, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

A new species of Hoplostethus from Sumatra , eastern Indian Ocean , with comments on its most similar congeners ( Trachichthyiformes : Trachichthyidae ) - Yo Su; Alexander N. Kotlyar; Hsiu‐Chin Lin; Toshio Kawai; Hsuan‐Ching Ho (Journal of Fish Biology, 2025)
A new species of the roughy fish genus Hoplostethus , subgenus Leiogaster , is described based on three specimens collected from Sumatra, Indonesia. This species can be distinguished from its congeners by the following characteristics: gular region covered with ctenoid scales; pelvic‐fin spine smooth on its anterior edge; head depth subequal or smaller than its length (37.2%–38.6% standard length [SL], or 94.7%–99.2% head length [HL]); pectoral‐fin length 35.6%–37.8% SL, reaching beyond a vertical through anal‐fin origin; abdominal scutes well developed, 12–16; pectoral‐fin rays uniformly black, 17–19; gill rakers on the first arch 6–7 + 1 + 13–14 = 21; pre‐dorsal scales 24–27; and pyloric caeca 32. A detailed description is provided along with comparisons with its congeners. Additionally, diagnostic characters of the congeners and literature records of Hoplostethus rubellopterus and Hoplostethus melanopus are discussed.

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Exploring the link between metformin use and adhesive capsulitis of the shoulder: a retrospective cohort study in Taiwan - Bing-Sian Lin; Wu-Chien Chien; Chieh-Hua Lu; Chi-Hsiang Chung; Chang-Huei Tsao; Tzu-Hsuan Weng; Ching-Yueh Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

Release of lead, copper, zinc from the initial corrosion of brass water meter in drinking water: Influences of solution composition and electrochemical characterization - Ching-Hsuan Hsu; Ding-Quan Ng; Yi-Pin Lin (Environmental Pollution, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

Mapping land-use and land-cover changes through the integration of satellite and airborne remote sensing data - Meng-Hsuan Lin; Ying-Tong Lin; Min-Lin Tsai; Yi-Ying Chen; Yi-Chun Chen; Hsueh-Ching Wang; Chi-Kuei Wang (Environmental Monitoring and Assessment, 2024)

Accumulated Hepatic Steatosis Grades Predicted by T2*-IDEAL Fat Fraction - Chang-Hsien Liu; Hing-Chiu Chang; Yi-Jui Liu; Wei-Ching Lin; Chi-Feng Hsieh; Te-Pao Lin; Cheng-Hsuan Juan; William Tzu-Liang; Chun-Jung Juan (Journal of Medical and Biological Engineering, 2023)

Livistona chinensis Water Extract has the Potential to Repair Thioacetamide-Induced Liver Fibrosis in Mice - San-Ho Hung; Tzu-Hsuan Hsu; Chun-Shien Wu; Yi-Ping Lin; Ching-Ting Wei; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

Hoplostethus roseus , a new roughy fish from the western Pacific based on morphology and DNA barcoding (family Trachichthyidae) - Yo Su; Hsiu‐Chin Lin; Hsuan‐Ching Ho (Journal of Fish Biology, 2022)
A new species of the roughy fish genus Hoplostethus is described from 11 types and a non‐type specimen collected from Taiwanese waters. It can be distinguished from its congeners by a combination of characters: pectoral‐fin rays 14–17 (modally 15–16); pyloric caeca 65–84; total gill rakers 19–20; predorsal scales 18–22; oral cavity, branchial chamber, top and underside of tongue, and peritoneum uniformly black; distal margin of membrane between dorsal‐fin spines black; caudal fin without a black margin; caudal‐fin base brownish. Comparisons of the new species with similar species are provided. DNA barcoding supports the monophyly of the new species, which appears to be closely related to Hoplostethus japonicus [average cytochrome c oxidase subunit I Kimura‐2‐parameter (COI K2P) distance of 4.1%].

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

A multidecadal change analysis for irrigation ponds in Taoyuan, Taiwan, using multisource data - Yen-Ching Chen; Wei-Chun Lin; Lin-Hsuan Hsiao; Ke-Sheng Cheng (Paddy and Water Environment, 2020)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

The Aso-Bridge coseismic landslide: a numerical investigation of failure and runout behavior using finite and discrete element methods - Ching Hung; Chih-Hsuan Liu; Guan-Wei Lin; Ben Leshchinsky (Bulletin of Engineering Geology and the Environment, 2019)

Preservation efficiency and storage effects for viable and culturable Staphylococcus aureus - Ching-Wen Chang; Meng-Hsuan Lin (Aerobiologia, 2019)

Soluble Epoxide Hydrolase Inhibition Attenuates MPTP-Induced Neurotoxicity in the Nigrostriatal Dopaminergic System: Involvement of α-Synuclein Aggregation and ER Stress - Hui-Ju Huang; Yi-Ting Wang; Hui-Ching Lin; Yi-Hsuan Lee; Anya Maan-Yuh Lin (Molecular Neurobiology, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Transcriptional analysis and functional characterization of XCC1294 gene encoding a GGDEF domain protein in Xanthomonas campestris pv. campestris - Yi-Min Hsiao; Wan-Ling Song; Chao-Tsai Liao; I-Hsuan Lin; Mei-Ying Pan; Ching-Fen Lin (Archives of Microbiology, 2012)

Gene inactivation in the citrus pathogenic fungus Alternaria alternata defect at the Ku70 locus associated with non-homologous end joining - Nan-Yi Wang; Siwy Ling Yang; Ching-Hsuan Lin; Kuang-Ren Chung (World Journal of Microbiology and Biotechnology, 2011)

Cellular Responses Required for Oxidative Stress Tolerance, Colonization, and Lesion Formation by the Necrotrophic Fungus Alternaria alternata in Citrus - Ching-Hsuan Lin; Siwy Ling Yang; Kuang-Ren Chung (Current Microbiology, 2011)

Bioavailability Effect of Methylprednisolone by Polymeric Micelles - Ching-Lin Chen; Shwu-Fen Chang; Daniel Lee; Lang-Yo Yang; Yi-Hsuan Lee; Chung Y. Hsu; Shwu-Jiuan Lin; Jiahorng Liaw (Pharmaceutical Research, 2008)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)